Metvan, bis(4,7-Dimethyl-1,10-phenanthroline)sulfatooxidovanadium(IV): DFT and Spectroscopic Study—Antitumor Action on Human Bone and Colorectal Cancer Cell Lines - León, Ignacio Esteban (2019)
The complex bis(4,7-dimethyl-1,10-phenantroline)sulfatooxidovanadium(IV), commonly known as Metvan, was prepared using a known synthetic procedure. Its optimized molecular structure was obtained by DFT calculations, as it was impossible to grow single crystals adequate for a crystallographic study. The complex was also characterized by a detailed analysis of its infrared spectrum, supported by the theoretical calculations, and also by some data derived from its Raman spectrum. In addition, cytotoxicity studies were performed using human osteosarcoma (MG-63) and human colorectal adenocarcinoma (HT-29) cell lines. The results show that Metvan impaired cell viability of both cancer cell lines in a low concentration range (0.25–5.0 μM).